A decision framework for inventory- and equipment-based supply chain finance solutions. Issue 4 (October 2021) - Ronchini, Alessio; Moretto, Antonella; Caniato, Federico
Abstract: Supply Chain Finance (SCF) has recently gained attention and relevance in both academia and practice. Indeed, during the pandemic crisis, firms in need for liquidity have increased the adoption of SCF solutions. Within SCF, a new stream of research is Asset-Based Lending (ABL), that encompasses inventory-based and equipment-based financing solutions. This study focuses on this topic by using a theoretical framework built on previous literature review and by adopting the theoretical lens of contingency theory. The case study methodology is adopted, with 25 observations collected by interviewing 15 providers and experts. For each of the 8 ABL solutions considered, it was possible to recognize contingent factors that favours the adoption, the objectives pursued by companies through their adoption and the stemming performance, in terms of benefits and costs. Moreover, ABL solutions were clustered in three typologies – the pledged, the efficient and the leasing – according to the objectives of adoption and the contingency factors. Six propositions and nine sub-propositions that explain the different typologies of adoption have been formulated. The typologies and the propositions can be used by managers as a guideline in the decision-making process, as they provide detailed information about the relevant variables to consider when adopting ABL solutions. Moreover, this study identifies future research directions, to assess the impact of each variable through quantitative methods from the adopter perspective, thus complementing our study. Highlights: We develop a framework to study both inventory- and equipment-based SCF solutions. We investigate objectives, costs, benefits of 8 asset-based lending (ABL) solutions. We identify contingency factors affecting the adoption process of ABL solutions. ABL solutions are clustered in 3 typologies of adoption patterns. Results led to formulating 6 propositions and 9 sub-propositions.